2021
DOI: 10.3390/met11071058
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Visual Appearance of AISI 430 Ferritic Stainless Steel Flat Sheets Manufactured by Cool Rolling and Bright Annealing

Abstract: This article reports on the relation between the surface topography and the optical reflectance, both total and diffuse, of different samples of AISI 430 ferritic stainless steel. Gaussian filters with different cutoff wavelengths were applied to the height maps of the surface topography of the samples, to separate the different scales of surface roughness involved in optical scattering in the visible range of the spectrum. Significant anisotropy, related to the rolling process, was found in the topography. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…All-hydrogen batch annealing of cold rolling can eliminate the residual stress, obtain recrystallized grains, and obtain a bright and smooth surface [17,18]. Thus, changing the batch-annealing process will change the microstructure [19,20], mechanical properties [21,22], and surface roughness [23,24] after batch annealing; these, in turn, may affect the microstructure, mechanical properties, and the oxide decarburized layer after austenitizing. A hot-stamping parts production company found that the oxide scale in the hot-stamping process decreased when the initial coldrolled sheet's batch-annealing temperature decreased.…”
Section: Introductionmentioning
confidence: 99%
“…All-hydrogen batch annealing of cold rolling can eliminate the residual stress, obtain recrystallized grains, and obtain a bright and smooth surface [17,18]. Thus, changing the batch-annealing process will change the microstructure [19,20], mechanical properties [21,22], and surface roughness [23,24] after batch annealing; these, in turn, may affect the microstructure, mechanical properties, and the oxide decarburized layer after austenitizing. A hot-stamping parts production company found that the oxide scale in the hot-stamping process decreased when the initial coldrolled sheet's batch-annealing temperature decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Ferritic stainless steel (FSS) has been applied in various industries [1][2][3]. It is considered as an interesting substitute for austenitic stainless steel because of its high thermal conductivity, small linear expansion, better resistance to chloride stress-corrosion cracking and low cost.…”
Section: Introductionmentioning
confidence: 99%